2016
DOI: 10.1515/acgeo-2016-0013
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Ionospheric Response to Geomagnetic Storms over a Low Latitude Station, Ile-Ife, Nigeria

Abstract: Due to several complexities associated with the equatorial ionosphere, and the significant role which the total electron content (TEC) variability plays in GPS signal transmission, there is the need to monitor irregularities in TEC during storm events. The GPS SCINDA receiver data at Ile-Ife, Nigeria, was analysed with a view to characterizing the ionospheric response to geomagnetic storms on 9 March and 1 October 2012. Presently, positive storm effects, peaks in TEC which were associated with prompt penetrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
(41 reference statements)
1
5
0
Order By: Relevance
“…Bagiya et al [19] in their study on geomagnetic storm of August 24, 2005 using GPS data from Rajkot station (22.29°N, 70.74°E); they observed that, TECv enhancement is due to prompt penetration of electric fields during the storm day and thermospheric composition changes and disturbance dynamo electric fields on the preceding recovery day. Similar results were also reported by Jimoh et al [20] on their study on investigation of ionospheric response to geomagnetic storms over a low latitude station, Ile-Ife, Nigeria. They attributed this with the high energy input at high latitudes that produces traveling ionospheric disturbances (TIDs).…”
Section: Discussionsupporting
confidence: 90%
“…Bagiya et al [19] in their study on geomagnetic storm of August 24, 2005 using GPS data from Rajkot station (22.29°N, 70.74°E); they observed that, TECv enhancement is due to prompt penetration of electric fields during the storm day and thermospheric composition changes and disturbance dynamo electric fields on the preceding recovery day. Similar results were also reported by Jimoh et al [20] on their study on investigation of ionospheric response to geomagnetic storms over a low latitude station, Ile-Ife, Nigeria. They attributed this with the high energy input at high latitudes that produces traveling ionospheric disturbances (TIDs).…”
Section: Discussionsupporting
confidence: 90%
“…In the absence of electric field measurements, sudden increase (decrease) in AE index and abrupt decrease (increase) in Dst index are good indicators to determine the strength, polarities, and time of penetration of electric fields into the equatorial and low latitudes (Abdu, ; Fejer & Scherliess, ; Huang, ; Huang et al, ; Tulasi Ram et al, ). Besides the rate of Dst ( Dst / dt ) is also a good proxy that have been used in the past to serve this purpose (Jain et al, ; Jimoh et al, ; Tulasi Ram et al, ). The AE in Figure a had a sudden increase from 1,400 to 2,400 nT and Dst / dt showed a rapid decrease (~41 nT/hr) at ~2330 UT on 7 September, which suggests that the southward turning of IMF‐ B z with minimum value of ~−30 nT created the undershielding condition that gave rise to PPEF at the low latitudes around 2330 UT.…”
Section: Discussionmentioning
confidence: 99%
“…Journal of Geophysical Research: Space Physics Ram et al, 2008). Besides the rate of Dst (Dst/dt) is also a good proxy that have been used in the past to serve this purpose (Jain et al, 2010;Jimoh et al, 2016;Tulasi Ram et al, 2008). The AE in Figure 1a had a sudden increase from 1,400 to 2,400 nT and Dst/dt showed a rapid decrease (~41 nT/hr) at~2330 UT on 7 September, which suggests that the southward turning of IMF-B z with minimum value of~−30 nT created the undershielding condition that gave rise to PPEF at the low latitudes around 2330 UT.…”
Section: 1029/2019ja026590mentioning
confidence: 99%
See 1 more Smart Citation
“…Geomagnetic storms usually comprise of three phases: initial, main, and recovery phases [6,11]. Different processes and interactions are at play, depending on the prevalent geophysical and interplanetary conditions during each phase of a geomagnetic storm [12][13][14][15][16][17][18]. The mechanisms responsible for total electron content (TEC) enhancements during the initial and main phases are widely reported [8,[19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%